'No-touch' breast-implant insertion device - Ameen, Shaa'ista (Division of Biomedical Engineering, 2016)
Capsular Contracture (CC) has been identified as the major cause of breast-implant failures and subsequent discomfort, pain and shape deformation following cosmetic breast implantation procedures. It has been documented that CC is primarily due to bacteria which are transmitted in the breast-cavity through conventional implantation. A 'no-touch' implant insertion technique has therefore been identified as the optimal method in potentially reducing CC rates. This describes an implant delivery without the implant ever touching: gloves (even during post-insertion implant orientation assessments), retractors or the patient's skin and breast-tissue; which is inherently unachievable with the traditional finger-manipulation method. To date, the most significant improvement in the insertion process has been a 'minimal-touch' technique, i.e. with the Keller-Funnel. This study was therefore in the design and development of a safe 'no-touch' insertion device for the delivery of silicone breast-implants. Parameters included a horizontal 45 mm incision, which can stretch up to a maximum vertical central distance of 35 mm. The proposed design featured a positive-displacement method with: (a) pressurized air as the insertion 'force', (b) an inverting-bag (partially inserted with the implant) to eliminate direct glove/implant contact, and (c) a built-in retractor with a breast-cavity air-removal path to reduce implant insertion resistance due to trapped air. The implant, in the device, remains closed to the environment and separated from the wound margin thus, eliminating skin/implant contact and further providing wound protection. Finally, the design employed an eccentric funnel shape for device use at the inframammary incision site with a suggested subpectoral or submuscular pocket placement, i.e. to eliminate breast-tissue/implant contact. Through experimentation with various implant sizes, device dimensions were suitable for implant-volumes up to 428.57 cm3. A 1 bar air supply was used to test the prototype and prove the concept on a silicone cast breast-model. Leverage of the built-in retractor efficiently opened the incision for device placement multiple times and, the successful insertions of the implants and inverting-bag into the breast-model indicated that a 'no-touch' technique was achievable. This was at a maximum insertion time of 4.2 seconds, amongst eight implants ranging from 242 to 428.57 cm3. However, the continued post-insertion air supply resulted in inflation of the inverted bag in the breast. This is at a high risk of developing a thoracic wall deformity and/or embolism. Suggestions were made to improve the design and eliminate this fault.